Production, purification, and characterization of halotolerant lipase from Leuconostoc mesenteroides subsp. mesenteroides ATCC 8293 - Eko Sukohidayat, Nurfadhilah Hidayah (2018)
Halotolerant lipases are essential in several industries, particularly food industry due to their ability to withstand different salt concentrations. Food industry usually involves food fermentation process, which requires the enzymes to be active and stable in the presence of high salt concentration in order to carry out the process efficiently. To date, only few halotolerant lipases have been discovered and characterized. Thus, the present work was conducted in order to produce, purify, and characterize halotolerant lipases from L. mesenteroides subsp. mesenteroides ATCC 8293. Production of extracellular lipase from L. mesenteroides subsp. mesenteroides ATCC 8293 was optimized according to culture conditions (carbon sources, nitrogen sources, emulsifier, and surfactants) and physical parameters (temperature and pH) using the shake-flask fermentation system. It was observed that lipase production was optimized when the following culture composition was used: peptone, 0.2% (w/v), olive oil, 1.0% (v/v), monopotassium phosphate (KH2PO4) 0.5g, dipotassium phosphate (K2HPO4) 0.5g, sodium chloride (NaCl) 0.1g, calcium chloride (CaCl2) 0.1g, magnesium sulfate heptahydrate (MgSO4.7H2O) 0.5g, gum arabic, 0.1% (w/v) and Tween 80, 0.1% (v/v) per liter. The best physical parameters for maximum lipase production were at 30℃ and pH 6. Purification of lipases produced from L. mesenteroides subsp. mesenteroides ATCC 8293 was conducted using a novel aqueous two-phase system (ATPS) composed of Triton X-100 and maltitol. Although, the search for alternative components of ATPS has been widely investigated, little attention has been given to polyols as a component of a two-phase system. The ability of polyols to mimic the structure of water and maintain an artificial sphere of hydration around the macromolecules makes them a potential candidate as a phase separating agent in ATPS. Initially, the phase diagram of this system was constructed using different concentrations of Triton X-100 and maltitol based on turbidimetric titration method. The partitioning of lipases was then optimized according to several parameters, which were pH, temperature, and crude load. It was observed that lipases preferentially migrated to the Triton X-100 rich phase. Optimum lipase partitioning was achieved in ATPS at tie-line length of 46.4%, crude load of 20% at a temperature of 30℃ and pH 8 respectively. Purification of lipases using this system resulted in high lipase purification factor of 17.28 and lipase yield of 94.7%. The purified lipase showed aprominent band on SDS-PAGE with an estimated molecular weight of 50 kDa. Hence, this study demonstrated that Triton X- 100 and maltitol could be potentially used as an alternative ATPS in order to efficiently purify valuable enzymes. The purified lipases were then characterized on the basis of temperature, pH, and the presence of surfactants, metal ions as well as different salt concentrations. Optimum lipase activity was observed at 37℃ and pH 8 respectively. The purified lipase was also observed to be stable at temperature range of 30-60℃ and pH range of 6-11. Lipase exhibited enhanced activity in the presence of non-ionic surfactants, which were Triton X-100, Tween 80 and Tween 20, with increased activity up to 40%. Conversely, the presence of SDS, an anionic surfactant, inhibited 78% of the lipase activity. Metals ions such as Na+, Mg2+ K+ and Ca2+ stimulated lipase activity whereas divalent ions such as Zn+ and Cu2+ significantly reduced lipase activity by almost 50%. It was also observed that lipase activity was remarkably enhanced beyond 100% in the presence of different salt concentrations (0-10% w/v), thus confirming that lipase from L. mesenteroides subsp. mesenteroides ATCC 8293 is a halotolerant enzyme.